Nutcracker syndrome: a case report - Torres Avelar de Lima, Mateus; Neumann Tavares, Eduardo; Folador, Luciano; Mendes Knabben, Mariana; Bilycz Corrêa, Ricardo Henrique (Clinical and Biomedical Research, 2023)
A 35-year-old woman felt left flank and left lower quadrant abdominal pain daily for the past six months, besides nausea, macroscopic hematuria, and shortness of breath. These symptoms progressively worsened until activities such as eating or working were significantly impaired. She investigated these symptoms in various medical institutions during this period, but no diagnosis was made. [Abstract truncated]